Correction: Plasma electrolysis of cellulose in polar aprotic solvents for production of levoglucosenone. Issue 24 (26th November 2020) - A, Lusi; Radhakrishnan, Harish; Hu, Haiyang; Hu, Hui; Bai, Xianglan
Abstract : Correction for 'Plasma electrolysis of cellulose in polar aprotic solvents for production of levoglucosenone' by Lusi A et al., Green Chem., 2020, 22, 7871–7883. DOI: ; 10.1039/D0GC02813D .